Integrative GWAS and transcriptomics reveal GhAMT2 as a key regulator of cotton resistance to Verticillium wilt - Wang, Long; Yang, Yonglin; Qin, Jianghong; Ma, Qifeng; Qiao, Kaikai; Fan, Shuli; Qu, Yanying (Frontiers in Plant Science, 2025)
IntroductionVerticillium wilt, incited by the soilborne fungus Verticillium dahliae, is a severe threat to global cotton (Gossypium spp.) production, resulting in significant yield losses and reduced fiber quality.MethodsTo uncover the genetic and molecular basis of resistance to this devastating disease, we combined genome-wide association study (GWAS) and transcriptomic analyses in a natural population of 355 upland cotton accessions.ResultsGWAS identified a stable major-effect quantitative trait locus (QTL), qVW-A01-2, on chromosome A01, which harbors the candidate gene GhAMT2, encoding a high-affinity ammonium transporter. Transcriptomic profiling revealed that GhAMT2 was significantly upregulated at 12 hours post-inoculation with V. dahliae, coinciding with the activation of immune signaling pathways. Weighted Gene Co-expression Network Analysis (WGCNA) further linked GhAMT2 to critical defense pathways, including lignin biosynthesis, salicylic acid signaling, and reactive oxygen species (ROS) homeostasis, suggesting its role in cell wall reinforcement and systemic immune responses. Functional validation through virus-induced gene silencing (VIGS) confirmed that silencing GhAMT2 compromised disease resistance. In contrast, transgenic Arabidopsis plants overexpressing GhAMT2 exhibited enhanced resistance to V. dahliae, demonstrating its essential role in defense regulation.DiscussionThese findings establish GhAMT2 as a key regulator of cotton resistance to Verticillium wilt and highlight its potential for marker-assisted breeding and genetic engineering to improve disease-resistant cotton varieties.